Modelling HIV/AIDS epidemics in Botswana and India: impact of interventions to prevent transmission - Nagelkerke Nico J.D; Jha Prabhat; Vlas Sake J. de; Korenromp Eline L.; Moses Stephen; Blanchard James F.; Plummer Frank A. (The World Health Organization, 2002)
OBJECTIVE: To describe a dynamic compartmental simulation model for Botswana and India, developed to identify the best strategies for preventing spread of HIV/AIDS. METHODS: The following interventions were considered: a behavioural intervention focused on female sex workers; a conventional programme for the treatment of sexually transmitted infections; a programme for the prevention of mother-to-child transmission; an antiretroviral treatment programme for the entire population, based on a single regimen; and an antiretroviral treatment programme for sex workers only, also based on a single regimen. FINDINGS: The interventions directed at sex workers as well as those dealing with sexually transmitted infections showed promise for long-term prevention of human immunodeficiency virus (HIV) infection, although their relative ranking was uncertain. In India, a sex worker intervention would drive the epidemic to extinction. In Botswana none of the interventions alone would achieve this, although the prevalence of HIV would be reduced by almost 50%. Mother-to-child transmission programmes could reduce HIV transmission to infants, but would have no impact on the epidemic itself. In the long run, interventions targeting sexual transmission would be even more effective in reducing the number of HIV-infected children than mother-to-child transmission programmes. Antiretroviral therapy would prevent transmission in the short term, but eventually its effects would wane because of the development of drug resistance. CONCLUSION: Depending on the country and how the antiretroviral therapy was targeted, 25-100% of HIV cases would be drug- resistant after 30 years of use.